2009
DOI: 10.2165/00002018-200932050-00006
|View full text |Cite
|
Sign up to set email alerts
|

Avoidability of Adverse Drug Reactions Spontaneously Reported to a French Regional Drug Monitoring Centre

Abstract: Preventive actions should focus on more systematic allergy checks when prescribing drugs and on dose adaptation in cases of altered renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 48 publications
3
20
0
2
Order By: Relevance
“…This study showed that in spontaneously reported ADRs in Sweden a total of 14% was considered preventable, a figure which is in accordance with a similar study from France [12].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study showed that in spontaneously reported ADRs in Sweden a total of 14% was considered preventable, a figure which is in accordance with a similar study from France [12].…”
Section: Discussionsupporting
confidence: 92%
“…The classification system used in our study was related to the objectives of the study. A study focusing on preventable ADRs due to inappropriate prescribing have used a slightly different classification system [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results do not support a causal role of serum uric acid for type 2 diabetes and hence do not encourage the initiation of clinical trials or an expansion of serum-uric-acid-lowering interventions with the aim of preventing type 2 diabetes. This might be of major relevance as allopurinol is one of the drugs most frequently involved in adverse reactions following inappropriate prescription [35], which might in part be due to confusion by the ongoing discussion on a causal role of serum uric acid for type 2 diabetes and other metabolic disease [36]. However, some of the non-pharmacological interventions recommended for the lowering of serum uric acid levels, such as weight loss, diet modifications, restriction of alcohol consumption and physical exercise, have positive effects beyond the lowering of serum uric acid and are clearly appropriate in metabolic high-risk individuals [37].…”
Section: Discussionmentioning
confidence: 99%